Digitalização do patrimônio cultural baseado em escaneamento de alta resolução - Rubens, Tallis Deyvide Maia (2023)
The preservation of cultural architectural heritage is a relevant concern due to the problems of deterioration and destruction faced by these structures. The lack of accurate and detailed documentation, together with the limitations of traditional techniques, hinders the proper preservation of these buildings. However, technological advances such as laser scanning and three-dimensional processing tools offer promising solutions for the acquisition, visualization and dissemination of accurate data, overcoming the limitations of conventional approaches. The use of three-dimensional models allows effective communication about the physical state of historic buildings, including deformations, damages and other relevant aspects. In addition, the Building Information Modeling (BIM) methodology has evolved to the specific application in historic buildings, known as HBIM, considering geometric, topological, semantic and graphical information of the building components, as well as their historical and artistic value. The application of these technologies, such as laser scanning and HBIM, in the preservation of historic buildings brings significant economic benefits. They provide accurate information for proper budgeting, strategic maintenance planning, simulation of interventions and efficient collaboration between professionals. This dissertation work has as main objective to develop strategies for the digitization of cultural heritage integrated with high resolution point cloud technology and HBIM. To achieve this objective, the specific objectives include reviewing and analyzing the main heritage digitization techniques, developing strategies for the application of HBIM methodology and cloud data collection, as well as analyzing and comparing the accuracy of 3D and 2D models. With the implementation of these strategies, it is expected to obtain a more complete and accurate representation of historic buildings, contributing to the proper preservation of cultural heritage. Furthermore, the application of these technologies offers economic benefits and agility in surveys, allowing a more efficient financial management of maintenance activities and promoting resource savings. The digitization of cultural heritage through high-resolution scanning and HBIM has the potential to transform the way historic structures are preserved, documented and made available for study and appreciation.